A Virtual Noninvasive Way of Constructing a Nasoalveolar Molding Plate for Cleft Babies, Using Intraoral Scanners, CAD, and Prosthetic Milling. (February 2020) - Shanbhag, Gajanan; Pandey, Swapnil; Mehta, Nirali; Kini, Yogesh; Kini, Ashwini
Presurgical nasoalveolar molding (PNAM) is a key step in the early management of cleft babies. It involves making an impression of the alveolar segments and the lip elements, after which an appliance is fabricated and activated to achieve optimal alveolar and nasal positions for a superior surgical result. These appliances are fabricated and activated in babies as young as 10 days, and the molding is ideally carried on till the baby is ready for the primary lip repair. This article outlines in detail a digital method of fabricating the PNAM appliance using a combination of intraoral scans, computer-assisted digital software, and computer-assisted machining, facilitated by milling machines. This process obviates impression making and the subsequent laboratory procedures.